2008
DOI: 10.1523/jneurosci.2537-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Suppressor Schwannomin/Merlin Is Critical for the Organization of Schwann Cell Contacts in Peripheral Nerves

Abstract: Schwannomin/merlin is the product of a tumor suppressor gene mutated in neurofibromatosis type 2 (NF2). Although the consequences of NF2 mutations on Schwann cell proliferation are well established, the physiological role of schwannomin in differentiated cells is not known. To unravel this role, we studied peripheral nerves in mice overexpressing in Schwann cells schwannomin with a deletion occurring in NF2 patients (P0 -SCH-⌬39 -121) or a C-terminal deletion. The myelin sheath and nodes of Ranvier were essent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 56 publications
5
25
0
Order By: Relevance
“…Interestingly, EdU-uptake was not significantly greater in normal, uninjured SCs from P0SchΔ39-121 mice compared with wild-type mice suggesting that loss of merlin function alone is not sufficient to drive peripheral nerve SCs into a significant hyperplastic response. Indeed, immmunolabeling and ultrastructural studies identified myelination abnormalities in sciatic nerves from P0SchΔ39-121 mice but did not reveal significant SC hyperplasia within the peripheral nerve (Denisenko et al, 2008). Rather, SC hyperplasia in P0SchΔ39-121 mice is found in foci near or within sensory ganglia and skeletal muscle (Giovannini et al, 2014), consistent with the observation that most schwannomas arise within sensory ganglia (Tryggvason et al, 2012), and suggesting that intraganglionic SCs are particularly sensitive to merlin status.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, EdU-uptake was not significantly greater in normal, uninjured SCs from P0SchΔ39-121 mice compared with wild-type mice suggesting that loss of merlin function alone is not sufficient to drive peripheral nerve SCs into a significant hyperplastic response. Indeed, immmunolabeling and ultrastructural studies identified myelination abnormalities in sciatic nerves from P0SchΔ39-121 mice but did not reveal significant SC hyperplasia within the peripheral nerve (Denisenko et al, 2008). Rather, SC hyperplasia in P0SchΔ39-121 mice is found in foci near or within sensory ganglia and skeletal muscle (Giovannini et al, 2014), consistent with the observation that most schwannomas arise within sensory ganglia (Tryggvason et al, 2012), and suggesting that intraganglionic SCs are particularly sensitive to merlin status.…”
Section: Discussionmentioning
confidence: 99%
“…Ppp1r14a can promote tumorigenesis by regulating activity of the Nf2/ Merlin tumor suppressor by means of myosin phosphatase (Jin et al, 2006). Nf2/Merlin has been implicated in control of Schwann cell number and organization of Schwann cell contact with axons (Scherer et al, 2001;Denisenko et al, 2008), but a function has not been described for oligodendrocytes. MID1 interacting protein 1b (mid1-ip1b, RefSeq:NM_200832, probe set Dr.25285.1.S1) is expressed by both oligodendrocytes (Figs.…”
Section: Validation Of Oligodendrocyte Gene Identification By In Situmentioning
confidence: 99%
“…Merlin is encoded by the tumor suppressor gene NF2 (implicated in neurofibromatosis type 2 tumors) and is important for the formation of axon–glial junctions174…”
mentioning
confidence: 99%